2023
DOI: 10.1108/prr-08-2022-0125
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors influencing investment decision making: a multi group analysis

Abstract: PurposeStock markets are considered as the largest and most important units for the development and growth of the economy. The present study attempts to provide a comprehensive view of factors influencing investment decision making process of stock market investors. A multi group analysis of gender is also carried out on the proposed model.Design/methodology/approachThe data of 402 valid responses are collected through structured questionnaires from individual investors of North India. SPSS 23 is used to do th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Advocate recommendations comprising suggestions from relatives, friends, family, brokers, financial planners, news channels, and so on. carry considerable weight in investing decisions, albeit to a lesser extent than the company's reputation and financial and neutral information, aligning with existing literature (Ali & Tariq, 2013;Brijlal, 2007;Khawaja & Alharbi, 2021;Sachdeva & Lehal, 2023). As highlighted by Hoffmann et al (2006), these social interactions play a significant role by mitigating uncertainty surrounding investing decisions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Advocate recommendations comprising suggestions from relatives, friends, family, brokers, financial planners, news channels, and so on. carry considerable weight in investing decisions, albeit to a lesser extent than the company's reputation and financial and neutral information, aligning with existing literature (Ali & Tariq, 2013;Brijlal, 2007;Khawaja & Alharbi, 2021;Sachdeva & Lehal, 2023). As highlighted by Hoffmann et al (2006), these social interactions play a significant role by mitigating uncertainty surrounding investing decisions.…”
Section: Discussionsupporting
confidence: 74%
“…Khawaja and Alharbi (2021) noted that while all five factors of investment decisions were significantly related to investor behavior, neutral information was the most important factor among others for Saudi investors. Sachdeva and Lehal (2023) found all five variables to be influencing the investment decisions of Indian investors. Ali and Tariq (2013) concluded that only self-image/firm image, neutral information, and advocate information significantly influenced the investment decisions of investors whereas, accounting information, classical wealth maximization, and personal financial needs were insignificant.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Subjective norms refer to a person's perception of the views and expectations of important people in their social environment, such as family, friends, or society. But keep in mind that other factors such as attitude, behavioral control, and quality of information can also affect one's sharia investment decision (Sachdeva, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis focuses on demographic dimensions including Gender, Age, Education, Occupation, Investment Motives, and Holdings of hydropower shares, aiming to explore their potential impact on individuals' decision-making concerning hydropower investments. (Jawaheer & Manual, 2016), age group (Joshi, 2018), and educational background (Maharjan et al, 2022) though Sachdeva and Lehal (2023) found no gender-based differences in investment choices. This means that investors with diverse demographic characteristics make different investment decisions for hydropower IPOs.…”
Section: One-sample T-test and Anova Testmentioning
confidence: 91%
“…While investors demonstrate some understanding of financial diversification and fundamental analysis, their decisions are influenced by education levels, age, and experience. Highlighting the research gap in prior studies, Sachdeva and Lehal (2023) identified the various influential factors in investment decision-making, emphasizing the importance of firm image. However, literature in Nepal lacks comprehensive studies on IPO responses and investment determinants beyond the financial sectors, which neglects other listed industries.…”
Section: Marketabilitymentioning
confidence: 99%